Design of a Local Game News Website Using the Waterfall Method and the Laravel Framework - Royan Habibie Sukarna; Fatwaraga Rafsanjani; Fitri Damyati; Haries Anom Susetyo Aji Nugroho (Jurnal Teknologi Informatika dan Komputer, 2026)
The video game industry in Indonesia is showing an upward trend, marked by the emergence of various local game developers and growing public interest. However, the availability of information platforms specifically dedicated to local games remains limited and scattered across various sources. This situation makes it difficult to access structured and centralized information. This study aims to design and develop a web-based news platform focusing on local Indonesian video games using the Waterfall methodology and Laravel framework. The development process follows a structured approach including requirement analysis, system design, implementation, and testing. Data were collected through user preference questionnaires, observation of similar websites, and post-development evaluation. The system was developed with core features such as responsive interface, search functionality, and SEO optimization. Black-box testing results show that all system functionalities operate correctly. User evaluation involving 25 indicators resulted in a satisfaction score of 90.8% with an average rating of 4.54 out of 5. These results indicate that the system is effective, user-friendly, and meets user needs. The study concludes that the Waterfall method is suitable for structured web development and Laravel supports efficient system implementation.